2016
DOI: 10.3329/bsmmuj.v9i3.29462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical and radiological outcomes of mineral trioxide aggregate and calcium hydroxide as indirect pulp capping agents in the treatment of deep carious lesion of permanent teeth

Abstract: <p>The maintenance of pulp vitality and conduction of reparative dentin can be possible by indirect pulp capping with mineral trioxide aggregate (MTA) and calcium hydroxide as pulp capping agents. The objective of the study is to assess the clinical and radiological outcomes of MTA and calcium hydroxide as indirect pulp capping agents in deep carious lesions of permanent teeth. The present study included 50 permanent teeth having deep carious lesions with reversible pulp status were selected and then ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Also. Sultana et al 15 compared mineral trioxide aggregate and calcium hydroxide as capping materials. They showed that at 3 months, reparative dentin was formed in 17 teeth (of 25 teeth) in the calcium hydroxide group and at 6 and 12 months, 19 treated teeth showed evident of reparative dentin formation.…”
Section: Clinical Parameter Resultsmentioning
confidence: 99%
“…Also. Sultana et al 15 compared mineral trioxide aggregate and calcium hydroxide as capping materials. They showed that at 3 months, reparative dentin was formed in 17 teeth (of 25 teeth) in the calcium hydroxide group and at 6 and 12 months, 19 treated teeth showed evident of reparative dentin formation.…”
Section: Clinical Parameter Resultsmentioning
confidence: 99%
“…8 It is also capable to protect the pulp when used as pulp capping agent, repair of the periodontium and new cementum formation over the material, and promote the growth of the cementum and formation of the bone. 8, 9 MTA experimentally showed better sealing ability than that of other materials such as amalgam, zinc oxide eugenol cement, resin modified cement and IRM. 9-12 Therefore, it is considered that MTA may also be suitable for closing the communication between the pulp chamber and the underlying periodontal tissues.…”
Section: Introductionmentioning
confidence: 86%
“…Ridwana Kawsar (MS Resident): There are cases of pulpitis when there isn't contamination of pulp with bacteria and can be preserved by some pulp capping or lining materials. 3,4 Here, most of the occlusal pulp tissue was necrosed and contaminated. So, the pulp can't be preserved and there is no chance to be reversed into a normal pulp.…”
Section: Reversible Pulpitismentioning
confidence: 98%